Of Pirates and Institutions (KULT_online, 2023)
The Punishment of Pirates by Matthew Norton takes the equal parts fascinating and slippery phenomenon of pirates as a means through which to glean how institutions shape the social world. Operating on both the level of historical narrative of the specific period of the long seventeenth century, and the level of sociological analysis of the discursive and interpretive underpinnings of legal systems in general, the book offers a wealth of historical and sociological insight. In addition, it is written in language both accessible and precise, making it a pleasure to read.